2019
DOI: 10.3389/fvets.2019.00138
|View full text |Cite
|
Sign up to set email alerts
|

Taking Dogs Into the Office: A Novel Strategy for Promoting Work Engagement, Commitment and Quality of Life

Abstract: Despite growing interest in “take your dog to work” days and the wellbeing benefits associated with interactions with a friendly dog (e.g., animal-assisted activities), there has been little quantification of the benefits of this. We analyzed responses to work-related (work engagement, turnover intention, work-based friendship acuity, social media use, and work-related quality of life) and dog-related (pet dog attachment and dog general health) scales from 749 employees. The predominantly female sample was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 90 publications
1
19
0
1
Order By: Relevance
“…While all of these factors might relate to job satisfaction, engagement, and turnover intentions, surprisingly, little research has addressed the topic. Hall and Mills [38] found significantly higher self-reported work engagement and lower turnover intention when petfriendly policies are in place. This takes further the findings of Barker [46], who reported that employees who are allowed to bring their pets to work scored higher on multiple job satisfaction scales.…”
Section: Dogs In the Workplacementioning
confidence: 96%
See 4 more Smart Citations
“…While all of these factors might relate to job satisfaction, engagement, and turnover intentions, surprisingly, little research has addressed the topic. Hall and Mills [38] found significantly higher self-reported work engagement and lower turnover intention when petfriendly policies are in place. This takes further the findings of Barker [46], who reported that employees who are allowed to bring their pets to work scored higher on multiple job satisfaction scales.…”
Section: Dogs In the Workplacementioning
confidence: 96%
“…In addition, dogs can also have positive influences on group dynamics, social interactions, and social behaviors [34,35], and trust is rated higher in groups in which a dog is present [34]. Dogs tend to improve the quality of social interactions in group therapy settings [35], with strangers and also with friends and acquaintances, which even leads to friendships and more social support in groups, thereby influencing long-term relationships in communities [36][37][38]. This might be related to a dog-related increase of oxytocin in humans, which is linked to an increase of pro-social behavior [39].…”
Section: Theoretical Background 21 Dogs and Humans-in Generalmentioning
confidence: 99%
See 3 more Smart Citations